Selected methods of conservative treatment in painful hallux valgus therapy - Katarzyna Wódka; Agnieszka Jankowicz-Szymańska; Eliza Smoła; Marta Bibro (University of Applied Sciences in Tarnow, Poland, 2020)
Hallux valgus is one of the most common deformities within forefoot region. Reasons for this deformity are not entirely clear. The available literature lists both internal and external factors. Researchers dealing with hallux valgus emphasize that this deformation is accompanied by pain, reduced quality of life, changed foot statics, cosmetic problems and problems with buying the right footwear. The occurrence of pain may significantly affect the quality of everyday functioning and the broadly understood quality of life. The purpose of the following publication is to review selected interactions in the area of physiotherapy and orthopedic measures in the therapy of people reporting pain within the hallux valgus region.